Perkembangan Kosakata Bahasa Arab Melalui IsytiqÄq - Albantani, Azkia Muharom; Fauziah, Afwa Uzna; Sumiantia, Iis (Departemen Pendidikan Bahasa Arab, 2020)
This paper aims to examine the development of Arabic vocabulary through isytiqÄq kabÄ«r, akbar, and kubbÄr. IsytiqÄq or derivation has appeared among Arabic linguists from the beginning of the third century hijriah until the middle of the end of the fourth century hijriah. The qualitative research method (al-bahts al-kayfi) with the type of library research is used in this paper to examine library materials related to the writing theme. The study results show that the type of isytiqÄq kabÄ«r is the same as taqlÄ«b (change), the type of isytiqÄq akbar is the same as ibdal, and the type of isytiqÄq kubbÄr is the same as naht (acronym). The three isytiqÄq have differences, namely; isytiqÄq kabÄ«r / akbar is to form various syllables from a syllable consisting of three phonemes, but still has elements of the same meaning. The similarity in meaning is because the word formed comes from a root word with the same phoneme. While isytiqÄq kubbÄr is to form a new word by abbreviating two or more words, which results in an abbreviated word meaning.